SUBTITLING STRATEGIES APPLIED IN THE SUBTITLE OF THE MOVIE "COCO” FROM ENGLISH INTO INDONESIAN - Wati, Dessri Finiya; Made Puspani, Ida Ayu (Udayana Journal of Social Sciences and Humanities, 2024)
Abstract: This study is entitled Subtitling Strategies Applied in The Subtitle of The Movie "Coco" From English Into Indonesian. This study is aimed to find out the subtitling strategies applied in translating the Indonesian subtitle of an English movie "COCO" and analyze the translation equivalence of the movie subtitle. All the data analyzed based on Theory of Subtitling Strategies according to Gottlieb and Theory of Translation Equivalence according to Nida. The source of the data taken from the downloaded Indonesian subtitle text of the original movie entitled COCO. Documentation method with note-taking technique were used to collect the data and to analyze using descriptive method with qualitative approach. The result of the data shows that the translator applied only eight of ten subtitling strategies. They are Expansion, Paraphrase, Transfer, Imitation, Transcription, Condensation, Decimation, and Deletion. The findings show that the translation of Coco's movie subtitle is equivalent. It shows that Dynamic and Formal equivalence applied in the translation. Keywords: translation, subtitling strategy, translation equivalence